Plato's Statesman and the nature of business leadership: An analysis from an ethical point of view - Klein, Sherwin (Journal of business ethics, 1988)
Plato's paradigm for statesmanship in the Statesman, the “weaving” of temperate and courageous properties, provides the contemporary business ethics theorist with an aid for determining certain problems and solutions with regard to business leadership. The history of American business values manifests the destructive, and especially unethical, effects of deviating from this paradigm by over-emphasizing one or the other of the above types of qualities. However, with the aid of Plato's model for leadership in the Statesman and suggestions from Peters and Waterman's In Search of Excellence, progress can be made towards constructing an adequate model for corporate leadership, especially from an ethical standpoint.